TRADITION OF RETURNING GOLD IN THE CANCELLATION OF ENGAGEMENTS FROM THE PERSPECTIVE OF 'URF: Socio-Legal Study in Acehnese Society - Yusuf, Muliana (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2026)
The tradition of engagement in Acehnese society is not only understood as a process leading to marriage but also carries social and customary legal consequences for the parties involved. A common practice in some Acehnese communities is the giving of gold during the engagement period, which is then associated with the obligation to return or compensate if the engagement is canceled. This study aims to analyze the practice of returning gold in the cancellation of engagements from the perspective of 'urf in Islamic law. The research uses a qualitative approach with a juridical-sociological method. Data were obtained through literature studies and analysis of the social practices of the Acehnese community related to engagement traditions. The results show that the practice of returning gold is seen as a form of strengthening commitment and protecting the dignity of the family. However, in practice, the application of different sanctions between men and women creates social inequality and has the potential to conflict with the principle of justice in Islamic law. From the perspective of ‘urf, this tradition can be accepted as long as it does not cause harm and does not contradict the principles of sharia. However, if the return of gold is made a burden that weighs heavily on one party, then the practice is closer to the category of ‘urf fasid. Therefore, a reconstruction of customary understanding that is more oriented towards public benefit, justice, and sharia values is required.